Seasonal and Spatial Variability in Patchiness of Microphytobenthos on Intertidal Flats From Sentinel-2 Satellite Imagery - Daggers, Tisja D.; Herman, Peter M. J.; van der Wal, Daphne (Frontiers in Marine Science, 2020)
Understanding the spatial structure of microphytobenthos (MPB) on intertidal flats is necessary to gain insight in the benthic community structure and ecosystem processes. The increasing availability of high resolution satellite sensors provides the opportunity to better understand spatial patterns of MPB on various (meter to km) scales. We tested how MPB patch size (indicated by the range derived from a semi-variogram) and degree of patchiness (indicated by the sill) vary as function of seasons, salinity, tidal flat type (muddy fringing versus sandy mid-channel tidal flats) or ecotopes (defined by hydrodynamics, silt content and elevation), in the Westerschelde estuary, the Netherlands. We used Sentinel-2 imagery (2016-2019) with 10 m spatial resolution to derive (omnidirectional) semi-variogram parameters from the NDVI (used as indicator for MPB biomass) and evaluated (seasonality in) patchiness of MPB in the different categories. We demonstrated that MPB patch size (the range) remains constant from winter to summer, while the sill increased from winter to summer. The location of patches on tidal flats was variable throughout the year and shows a remarkable similarity with seasonality in the spatial heterogeneity of the silt content on tidal flats. The patch size and degree of patchiness is higher on relatively sandy mid-channel tidal flats than on relatively silt rich fringing tidal flats. This implies that spatial patterning of MPB biomass on the meso scale is likely closely linked to abiotic conditions and that spreading processes or grazing activity play a minor role. We observed visually that some areas with a relatively high MPB biomass (‘patches’) remain visible throughout the year, while other patches were only present during a particular season.